Gas phase electrochemical conversion of humidified CO2 to CO and H2 on proton-exchange and alkaline anion-exchange membrane fuel cell reactors - Wang, Guoliang; Pan, Jian; Jiang, San Ping; Yang, H. (2018)
© 2017 Fuel cell reactors or electrolyzers based on alkaline anion-exchange membrane and proton exchange membrane (AAEM & PEM) are investigated for gas phase electrochemical conversion of humidified CO 2 under identical conditions, using conventional Pt/C, Pd/C and Cu/CNTs as cathodic catalysts. Humidified CO 2 can be converted to H 2 and CO via the AAEM based fuel cell reactors with an estimated onset potential of -1.0 V using Cu/CNT as cathodic catalyst, while PEM based fuel cell reactors can only produce H 2 under identical conditions. This can be attributed to the suppressed hydrogen evolution and enhanced CO 2 reduction in the case of AAEM based reactor. Remarkably, AAEM based reactor with Cu/CNT cathode catalysts shows a higher activity (8.88 µmol h -1 cm -2 ) to convert CO 2 to CO than that of Pd/C (7.59 µmol h -1 cm -2 ) and Pt/C (0.75 µmol h -1 cm -2 ) at the same catalyst loading. This study indicates that AAEM based reactor is able to realize the gas phase electrochemical conversion of CO 2 , providing a viable strategy for CO 2 utilization and conversion to useful fuels.